A study on work characteristics and morbidity pattern of coal mine workers in South India - Neelakanti, Rajashekar; Sriramula, Priyanka (International Journal Of Community Medicine And Public Health, 2019)
Background: Globally, coal mining is one of the dangerous occupations which leads to hazardous effects to coal mine workers due to production and dispersion of coal dust. These workers face more survival and working pressure than normal workers. Hypertension, diabetes and chronic respiratory symptoms are more prevalent in coal miners than normal population. This study was conducted with the objective to know the working pattern of coal mine workers and to know their habits and morbidity pattern. Methods: A descriptive study was conducted in one of the coal mines during October 2016 to December 2017. 846 coal mine workers were included in the study. Results: 480 (56.74%) workers belong to the age group of 50-60 yrs. Present study includes 696 underground mine workers and 150 surface workers. 222 (26.23%) workers had a habit of smoking, alcohol consumption is seen in 96 (11.35%) of surface workers and 480 (56.73%) of underground workers. In present study prevalence of hypertension is 19.15%, prevalence of diabetes is 16.31% and the prevalence of symptoms of chronic respiratory disease is 28.38%. Conclusions: The current study has shown a higher prevalence of diabetes than national prevalence and showed a lesser prevalence of hypertension than national prevalence which may be probably due to other causes rather than occupational stress alone. Morbidity is more than the normal population hence health education is done among workers regarding chronic diseases and their risk factors.